Problematika současné právní úpravy nadací - Franková, Eva (Univerzita Pardubice, 1999)
This article engage in the present legislation of the endowements, which are nonprofit organization, decribe the way of registration new endowements, the conditions and the demands for registrations new endowements. There is the possibilities of transformation the endowement to the common utility society in the next part this contribution. The last part improve the legislation of endowement, indicate of the questions and mystakes in this legislation.
Keywords: práva; legislativa; nadace; Neziskové organizace; právní úpravy